2000
DOI: 10.1152/ajpheart.2000.279.4.h1591
|View full text |Cite
|
Sign up to set email alerts
|

Skin microvascular adaptations during maturation and aging of hairless mice

Abstract: Using intravital fluorescence microscopy in the ears of hairless mice, we determined skin microvascular adaptations during the process of aging from juvenile to adult and senescent life (6-78 wk). Despite an increase of ear area within the first 36 wk, the number and branching pattern of both arteriolar and venular microvessels remained constant during the whole life period. Both arterioles and venules exhibited an increase in length, diameter, and intervascular distance up to the age of 36 wk. With the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
3
26
0
Order By: Relevance
“…In a previous investigation [18], we demonstrated that 75 % of immunocompetent homozygous hairless mice (skh-1) died a natural death within a 72-week period. Accordingly, 19-month-old (76-week-old) animals were considered to be senescent.…”
Section: Animalsmentioning
confidence: 89%
See 1 more Smart Citation
“…In a previous investigation [18], we demonstrated that 75 % of immunocompetent homozygous hairless mice (skh-1) died a natural death within a 72-week period. Accordingly, 19-month-old (76-week-old) animals were considered to be senescent.…”
Section: Animalsmentioning
confidence: 89%
“…Accordingly, 19-month-old (76-week-old) animals were considered to be senescent. In analogy with other previous studies [18], 2-month-and 10-month-old animals were considered adolescent and adult respectively.…”
Section: Animalsmentioning
confidence: 99%
“…We, therefore, accounted for two distinct conditions associated with skh-1-mice: (1) 75% of immunocompetent homozygous hairless mice (skh-1) died of a natural death within a 72-week period [15]. Accordingly, 19-month-old animals (76 weeks old) have to be regarded as senescent, whereas 2-and 10-month-old animals were considered adolescent and adult, respectively [15].…”
Section: Animalsmentioning
confidence: 99%
“…We, therefore, accounted for two distinct conditions associated with skh-1-mice: (1) 75% of immunocompetent homozygous hairless mice (skh-1) died of a natural death within a 72-week period [15]. Accordingly, 19-month-old animals (76 weeks old) have to be regarded as senescent, whereas 2-and 10-month-old animals were considered adolescent and adult, respectively [15]. (2) Furthermore, we rely on the fact that the absolute number and the general pattern of vessels within the defined tissue areas is fixed within the late juvenile growth phase [15].…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation